Prevalence and characteristics of tobacco and cannabis co-use in 15-year-old students in Slovenia - Koprivnikar, Helena (Obzornik zdravstvene nege, 2019)
Introduction: While the co-use of tobacco and cannabis is common among adolescents, no data on this topic is currently available for Slovenia. The purpose of this study was therefore to explore the prevalence and characteristics of tobacco and cannabis co-use in 15-year-old students in Slovenia.Methods: We analysed the data obtained from a representative sample of 15-year-old Slovene students (n = 1615) who took part in the 2014 Health Behaviour in School-Aged Children international cross-sectional survey, and performed a chi-square test and multivariate logistic regression analyses.Results: Lifetime tobacco and cannabis use was reported by 19.5 % of 15-year-old students with no gender difference (p = 0.108) and was associated with history of drunkenness (OR = 8.18, 95 % C.I. 5.74-11.64), friends' use of cannabis (OR = 3.93, 95 % C.I. 2.67-5.79) and tobacco (OR = 1.83, 95 % C. I. 1.25-2.69), and with lower perceived family support (OR = 0.88, 95 % C.I. 0.80-0.97). Current co-use was reported by 7.2 % with no gender difference (p = 0.136) and was associated with a history of drunkenness (OR = 8.06, 95 % C.I. 4.43-14.67), friends' use of cannabis (OR = 3.72, 95 % C.I. 2.23-6.19) and living in a reconstructed family (OR = 3.33, 95 % C. I. 1.74-6.40).Discussion and conclusion: Our study advocates for expanding preventive and cessation programmes from one to more psychoactive substances. Peers and family are the key factors which need to be addressed in these programmes. They can be reached through the school and healthcare systems. Environmental prevention measures, including legislative measures, create environments promoting healthy choices and thus contribute to the reduction of such co-use.
Keywords: adolescents; co-use; co-user characteristics; mladostniki; psihoaktivne snovi; psychoactive substances; souporaba; značilnosti souporabnika